Two-dimensional graphene nanomaterials for combined photothermal and chemotherapy-enhanced targeted therapy of breast cancer - Xiongjie Zhu; Juanjuan Lei; Chao Jiang; Zhaobi Fang; Wenkai Zhang; Zhe Yang; Rui Guo; Rui Xu; Xiaoshan Hu (Materials Today Bio)
Breast cancer is one of the most common malignant tumors in women, accounting for 7–10 % of all malignant tumors in the body. Second only to uterine cancer, it poses a significant threat to women's health. In this study, a two-dimensional material based on GO nanoparticles was designed to combine photothermal therapy (PTT) with chemotherapy for targeted treatment of breast cancer. Firstly, HPAA was grafted onto GO through an amide reaction after EDC/NHS activation. Secondly, RGD was attached to the amino group of HPAA. Finally, the chemotherapeutic drug doxorubicin was loaded through intermolecular interactions. In vitro results showed that the HPAA/GO-RGD@DOX exhibited a good photothermal effect and drug release profile, with greater drug release in acidic environments compared to neutral ones. Additionally, it accelerated the apoptosis of tumor cells under laser irradiation. Importantly, in vivo experiments demonstrated that HPAA/GO-RGD@DOX, when combined with laser irradiation, effectively targeted the tumor site and inhibited tumor growth. In conclusion, HPAA/GO-RGD@DOX exhibits high tumor targeting efficiency and a strong photothermal effect. This study suggests that the HPAA/GO-RGD@DOX composite holds great promise as a new type of functional 2D nanoparticle with photothermal capabilities for breast cancer therapy.